THE ROLE OF REVIEWING BUILDING STRUCTURES TO FULFILL REQUIREMENTS FOR STIFFNESS, STABILITY AND STRENGTH OF BUILDING STRUCTURES - Triastuti, Nusa Setiani; Indriasari, Indriasari (POLITEKNIK NEGERI JAKARTA, 2020)
Indonesia at the location of the earthquake All building structures must meet the structural requirements, namely stiffness, stability, strength. Review structures before building are built determine whether they meet the requirements Methodology Case studies based on secondary data. from the design consultantÂ The author analyzes with the help of structure software. The purpose of this research is to make sure the building structure meets the structural requirements before it is built. The author conducted a design review based on the Indonesian Code (SNI) Desain consultant dataÂ , building structure is still twist in shape mode 1 and 2 after checking in software. Then the authors review and improve mainly dimensions, reinforcement columns and add shear walls. As a result of the addition of shear walls and column changes, the structure meets the requirements of strength, stiffness and stability. Building structure does not occur twist in shape modes 1 and 2. That is the role of design structure review before it is built. To increase the stability of the structure at the bottom of the stairs out towards the back is given a retaining wall, overcoming the horizontal direction of active soil pressure, ground water and surface water from the direction of the hill.